2021
DOI: 10.1007/s11356-021-17827-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial analysis of the ecosystem service values in the Three Gorges Reservoir area of China based on land use change

Abstract: The Three Gorges Reservoir area (TGRA) has complex geological conditions and a fragile ecological environment. The construction of the Three Gorges Project triggered ecological and environmental issues and social disputes, which have attracted considerable attention in recent years. However, how the temporal and spatial characteristics of ecosystem service value (ESV) in the TGRA changed in each stage of the Three Gorges Project with the implementation of ecological restoration plans remains ambiguous. Based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
(59 reference statements)
2
12
1
Order By: Relevance
“…Additionally, water storage increased water area of the TG reservoir, resulting in a positive impact on GEP changes. The similar findings of X. Zhao et al (2022) proposed that the augmentation of water resources have played a crucial role in promoting ecosystem services. On the one hand, water bodies have powerful ecological functions, providing a wide range of essential productions and services (e.g., water supply, hydrological regulation and water purification), which are crucial for preserving ecosystems and supporting local income generation (D. Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally, water storage increased water area of the TG reservoir, resulting in a positive impact on GEP changes. The similar findings of X. Zhao et al (2022) proposed that the augmentation of water resources have played a crucial role in promoting ecosystem services. On the one hand, water bodies have powerful ecological functions, providing a wide range of essential productions and services (e.g., water supply, hydrological regulation and water purification), which are crucial for preserving ecosystems and supporting local income generation (D. Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…The similar findings of X. Zhao et al (2022) proposed that the augmentation of water resources have played a crucial role in promoting ecosystem services.…”
Section: Urbanization and Economic Developmentmentioning
confidence: 52%
“…The TGRA refers to the regions affected by inundation due to the construction of the Three Gorges Project of the Yangtze River. It is located at the joining of the Sichuan Basin and the middle and lower reaches of the Yangtze River Plain, from Yiling District in the east to Jiangjin District in the west, covering an area of about 58,000 km 2 [42]. Based on the unique characteristics of regional development, the National Main Functional Area Planning positions the TGRA as a key development area and a key ecological functional area.…”
Section: Study Areamentioning
confidence: 99%
“…The atrophy of water and reeds and sedges in wetland reserves were the main reasons for the decline in ESs in one study (Long et al, 2022). Forestland, water area, and saline–alkali land were the main factors affecting the change in the ES value of reservoirs, basins, and wetlands, respectively (He et al, 2022; Sun et al, 2021; Xiao et al, 2022; Xie et al, 2021; Zhang et al, 2019; Zhao et al, 2022). In addition, scholars have found that rural–urban fringe ecosystems with drastic changes in land use are often fragile, and the ES function is simple (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%